2013
DOI: 10.1002/wrna.1191
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of flavivirus RNA synthesis and capping

Abstract: RNA viruses, such as flaviviruses, are able to efficiently replicate and cap their RNA genomes in vertebrate and invertebrate cells. Flaviviruses use several specialized proteins to first make an uncapped negative strand copy of the viral genome that is used as a template for the synthesis of large numbers of capped genomic RNAs. Despite using relatively simple mechanisms to replicate their RNA genomes, there are significant gaps in our understanding of how flaviviruses switch between negative and positive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 89 publications
(118 reference statements)
0
29
0
Order By: Relevance
“…A previous study demonstrated that the synthesis of negative-sense RNA primarily depends on NS5 RdRp activity, whereas the synthesis of positive-sense RNA requires multiple additional enzymatic functions from both NS3 (helicase, ATPase, RNA triphosphatase) and NS5 (guanylyltransferase, methyltransferase) (46). Although there is no evidence so far showing that PKA directly phosphorylates NS5, it has been shown that NS5 could indeed be phosphorylated at Thr 449 in the RdRp fingers domain by protein kinase G, leading to the inactivation of its function (55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that the synthesis of negative-sense RNA primarily depends on NS5 RdRp activity, whereas the synthesis of positive-sense RNA requires multiple additional enzymatic functions from both NS3 (helicase, ATPase, RNA triphosphatase) and NS5 (guanylyltransferase, methyltransferase) (46). Although there is no evidence so far showing that PKA directly phosphorylates NS5, it has been shown that NS5 could indeed be phosphorylated at Thr 449 in the RdRp fingers domain by protein kinase G, leading to the inactivation of its function (55).…”
Section: Discussionmentioning
confidence: 99%
“…9C), confirming that PKI mainly affects negative-sense RNA synthesis. Since the negative-sense RNA of flaviviruses often requires NS5 RNA-dependent RNA polymerase (RdRp) activity (46), further investigation can focus on whether and how PKI suppresses the ZIKV NS5 RdRp function.…”
Section: Pki 14-22 Inhibits Zikv Replication By Inhibiting the Pka Pamentioning
confidence: 99%
“…Translation of the long open reading frame produces a large polyprotein that is cleaved by a combination of viral and host proteases to generate three structural proteins and seven nonstructural (NS) proteins (Chambers et al, 1990). The seven NS proteins make up the RNA replication complex that is responsible for generating both the minus- and positive-strands of RNA necessary to carry out the viral life cycle (Saeedi & Geiss, 2013; Westaway et al, 2003). …”
Section: Flavivirus Ns1 Protein: Oligomeric States Drive Functionalitmentioning
confidence: 99%
“…NS5-Pol (74 kDa) is connected via a flexible short linker to the N-terminal methyltransferase (MTase) domain (30 kDa), which contains two MTase activities and possibly a guanylyltransferase activity (GTase), thus incorporating three of the four reactions necessary to form a type-1 RNA cap at the 5’-end of the nascent +RNA strand [4,5]). The NS5-Pol domain alone displays de novo RdRp activity [9,2326].…”
Section: Regulatory Elements Within the Ns5 Polymerase Domainmentioning
confidence: 99%